Cross Cultural Educational Exchanges between Indonesia and Japan - Tati Rohayati (Studia Islamika, 2017)
Currently, Japan has become a country which has a big influence especially in South East Asia. They actively build bilateral and multilateral cooperation with other countries like establishing the Japan International Cooperation Agency (JICA) in August 1974. The cooperation has involved many sectors such as technology, politics, economy, social affairs and culture.On the ASEAN stage, Japan is actively promoting its culture to ASEAN countries, including Indonesia. One major program is “Pesantren Leaders’ Visit to Japan”. The program is a cooperation between the Japanese Embassy and the Center for the Study of Islam and Society (PPIM), UIN Syarif Hidayatullah Jakarta, which has run from 2004 until now.In the program, the Japanese Government every year invites several religious education leaders in Indonesia to observe the social and culture dynamics of the Japanese. Not only that, they are also invited to visit some schools, government offices, small and medium enterprises in Japan to see the latest productivity developments, including the problems and challanges they have in many sectors. As a result of its ongoing work, this bilateral program has produced a cross-cultural network and inter-faith dialogue among Islamic schools in Indonesia and Japan.DOI: 10.15408/sdi.v24i1.5152